Underlying resin infiltration and direct composite veneers for the treatment of severe white color alterations of the enamel: case report and 13-month follow-up - Sekundo, Caroline; Frese, Cornelia (Operative dentistry, 2020)
Pronounced white color alterations due to structural anomalies of the enamel are often insufficiently masked by bleaching techniques or resin infiltration procedures alone. This frequently leads to the choice of more invasive prosthetic restorations in order to correct tooth color and form. This article describes a minimally invasive treatment option for esthetic and functional rehabilitation in the case of a 13-year-old female patient with suspected severe fluorosis and misalignment of the anterior teeth. The restorations were performed using underlying resin infiltration to homogenize the tooth shade. In a second step, direct composite veneers were applied on top to attain a natural tooth color and adjust tooth alignment and form. By joining the two minimally and noninvasive techniques, this treatment option combines the directive for preservation of hard tooth structure while treating adolescents with the benefits of easy adaptation and repair when the occlusion is still in adjustment.